Characterization and Origin of Fibrinogen in Blood Platelets - James, Harold L.; Ganguly, Pankaj; Jackson, Carl W. (Thrombosis and Haemostasis, 1977)
The discovery of thrombin-clottable protein in platelet homogenates initiated studies on the location, properties, and origin of such material, the ultimate aim of which has been to define its physiologic role. It was established that fibrinogen is present both on the platelet membrane as well as in the cytoplasmic α-granules. The membrane-bound material is apparently fibrinogen adsorbed from plasma, while the intracellular fibrinogen appears to have unique biochemical and functional properties. Differences in properties observed between platelet fibrinogen and plasma fibrinogen are not due to in vitro modifications during handling. Whether the intracellular fibrinogen is synthesized in the platelet (or megakaryocyte) or whether it is derived through uptake and limited modification of plasma fibrinogen in vivo has remained an open question. Thus, to investigate the aspect of origin of platelet fibrinogen, radioactively-labelled fibrinogen was injected into rats, blood was collected at time intervals and the radioactivity in the subcellular fractions of platelets was examined. A part of the injected fibrinogen became associated with the platelets, but very little was found in the granule fraction. Previous findings on human platelet fibrinogen, together with the present data obtained using rats, suggest that platelet fibrinogen may not be derived from plasma fibrinogen in vivo. It thus is apparent that the intracellular fibrinogen is synthesized by a unique genetic mechanism. Molecular properties of fibrinogen derived from rat platelet granules were shown analogous to the properties of fibrinogen from human platelet granules. Fibrinogen of intracellular origin is less stable than its plasma counterpart. The results obtained by others in which identity of platelet and plasma fibrinogens was reported may be explained on the basis of recovery of only the fibrinogen component bound to the platelet membrane, which is adsorbed plasma fibrinogen. It is suggested that the term platelet fibrinogen may be used to denote that present in the α-granules, with the membrane-bound component being referred to as platelet-associated fibrinogen.